PENERAPAN PSIKOLOGI PAK BERLANDASKAN ROMA 10 :17 DALAM PERENCANAAN PEMBELAJARAN PAK UNTUK PENGUATAN IMAN - Hendra Saputra; Uli Saut Nainggolan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Christian Religious Education (PAK) plays a strategic role in fostering students’ faith holistically; however, in practice, learning often does not fully consider students’ psychological aspects. Romans 10:17 affirms that faith comes from hearing the word of Christ, thus requiring well-planned learning that provides meaningful learning experiences. This study aims to analyze the application of educational psychology based on Romans 10:17 in planning PAK learning to strengthen students’ faith. The method used is a qualitative descriptive approach through a literature study of theological and educational psychology sources. The research stages include data collection, reduction, categorization, and synthesis to identify the relationship between educational psychology principles and the theological foundation of Romans 10:17. The results show that integrating educational psychology into PAK lesson planning helps teachers understand students’ cognitive, affective, and spiritual development, making learning more meaningful, contextual, and transformative. Psychopedagogically designed learning creates a supportive environment that encourages the internalization of faith values. Therefore, PAK lesson planning that integrates educational psychology and is grounded in Romans 10:17 serves as an effective approach to strengthening students’ faith in a sustainable manner. ABSTRAK Pendidikan Agama Kristen (PAK) memiliki peran strategis dalam membentuk iman peserta didik secara holistik, namun dalam praktiknya pembelajaran sering kali belum sepenuhnya memperhatikan aspek psikologis peserta didik. Roma 10:17 menegaskan bahwa iman timbul dari pendengaran akan firman Kristus, sehingga diperlukan perencanaan pembelajaran yang mampu menghadirkan pengalaman belajar yang bermakna. Penelitian ini bertujuan untuk menganalisis penerapan psikologi pendidikan yang berlandaskan Roma 10:17 dalam perencanaan pembelajaran PAK untuk penguatan iman peserta didik. Metode yang digunakan adalah pendekatan kualitatif deskriptif melalui studi pustaka terhadap literatur teologis dan psikologi pendidikan. Tahapan penelitian meliputi pengumpulan data, reduksi, kategorisasi, dan sintesis untuk menemukan keterkaitan antara prinsip psikologi pendidikan dan dasar teologis Roma 10:17. Hasil penelitian menunjukkan bahwa integrasi psikologi pendidikan dalam perencanaan PAK membantu guru memahami perkembangan kognitif, afektif, dan spiritual peserta didik, sehingga pembelajaran menjadi lebih bermakna, kontekstual, dan transformatif. Pembelajaran yang dirancang secara psikopedagogis mampu menciptakan suasana yang suportif dan mendorong internalisasi nilai iman. Dengan demikian, perencanaan PAK yang berbasis psikologi pendidikan dan berlandaskan Roma 10:17 menjadi pendekatan yang efektif dalam memperkuat iman peserta didik secara berkelanjutan.